Analisa Penggunaan Media Sosial Dan Kesehatan Mental Remaja : Tinjauan Terhadap Pengaruh Konsumsi Dan Interaksi Online - AYUANDA, LEILA; Arifiana, Ratna; Kusuma, Nur; Sari, Laily Lolita (Jurnal Ilmiah Kesehatan, 2025)
In an era where social media use is increase massively, adolescents are one of the most affected groups. Adolescent mental health is a major concern because there are concerns about the negative impact of social media use on their psychological well-being. Although social media can be a useful means of communication, too much time spent on these platforms has been associated with increased symptoms of anxiety, depression, and other mental health problems in adolescents. This study aims to provide new contributions to the understanding of the relationship between social media use and adolescent mental health by specifically considering the influence of online content consumption and interaction. The sampling technique used purposive sampling in adolescents aged 13-18 years. The instrument used in the measurement was HADS. Data were analyzed using univariate and bivariate tests using the perason correlation test. The results of this study indicate that social media use has a complex impact on adolescent mental health. So it is important to manage the use of social media and encourage the active role of parents and educators in providing guidance to adolescents to use social media in a healthy way.